The Impact of Extracurricular Arts Education on Creativity Among High School Students - Liben Prazna; Filiyana Isy (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
This research investigates the influence of extracurricular arts and culture programs on high school students' creativity. Through a mixed-methods approach combining quantitative analyses and qualitative insights, we explore the transformative potential of arts education in shaping students' cognitive, socio-emotional, and personal development. Our findings reveal significant differences in creativity scores between students participating in arts programs and their non-participating peers, indicating a positive association between engagement in arts education and creative thinking skills. Longitudinal tracking of participants over time demonstrates the sustained effects of arts programs on students' creative development, highlighting the long-term benefits of extracurricular arts and culture programs. Qualitative insights gleaned from interviews provide rich narratives that illuminate the socio-emotional dimensions of arts education, including feelings of empowerment, self-expression, and belonging among participants. Integrating quantitative analyses with qualitative insights offers a comprehensive understanding of the mechanisms underlying the impact of arts education on creativity. While our research contributes valuable insights into the transformative power of extracurricular arts and culture programs, it is essential to acknowledge limitations such as potential selection bias and reliance on self-report measures. Addressing these limitations through methodological refinements and replication studies will be crucial for advancing our understanding of the complex relationship between arts education and creativity.